2013
DOI: 10.1055/s-0033-1345721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of HBV-Associated Hepatocarcinogenesis

Abstract: Hepatitis B virus (HBV) contributes to hepatocellular carcinoma (HCC) development through direct and indirect mechanisms. HBV-DNA integration into the host genome occurs at early steps of clonal tumor expansion and induces both genomic instability and direct insertional mutagenesis of diverse cancer-related genes. Prolonged expression of the viral regulatory protein HBx and the large envelope protein deregulate the cellular transcription program and proliferation control and sensitize liver cells to carcinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 94 publications
1
91
0
1
Order By: Relevance
“…HBx is an important oncoprotein involved in the development of HBV-related HCC. 16 We found that HBx-induced HCC cell proliferation, colony formation, and tumor growth were significantly compromised by PP2Ac knockdown, suggesting a mediating role for PP2Ac in the pathogenesis of HBV-related HCC. Clinical data revealed that high PP2Ac expression was significantly associated with histological grade, TNM stage, intrahepatic metastasis, and early recurrence.…”
Section: Discussionmentioning
confidence: 74%
“…HBx is an important oncoprotein involved in the development of HBV-related HCC. 16 We found that HBx-induced HCC cell proliferation, colony formation, and tumor growth were significantly compromised by PP2Ac knockdown, suggesting a mediating role for PP2Ac in the pathogenesis of HBV-related HCC. Clinical data revealed that high PP2Ac expression was significantly associated with histological grade, TNM stage, intrahepatic metastasis, and early recurrence.…”
Section: Discussionmentioning
confidence: 74%
“…Viruses that integrate their own DNA into the host's genome can initiate insertional mutagenesis. Hepatitis B virus and certain oncogenic avian viruses provide examples of viruses that can spur carcinogenesis, at least partially, through this mechanism (5,6). Therefore, studies that examine only RNA-Seq data may be unable to completely ascertain whether such viruses could be contributing to carcinogenesis.…”
mentioning
confidence: 99%
“…have also claimed that HBV subgenotypes and mutations in enhancer II, basal core promoter, and precore regions of HBV in relation to risks of liver cirrhosis (LC) and HCC in Southeast China. As claimed by Guerrieri et al (2013) and Yang et al (2013) the mutated YMDD motifs of HBV infection may contributes HCC by inducing both genomic instability and direct insertional mutagenesis of cancer related genes at the early steps of clonal tumor expansion and promote its tumor development by eliciting epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%